Povezanost statusa telesne teže in športne aktivnosti s telesno samopodobo učencev 2. in 3. triletja - Pepevnik, Darko (Revija za elementarno izobraževanje, 2008)
Relationships Between Body Weight Status, Sport Activities and the Physical Self-Image of Pupils in the 2nd and 3rd Triads. In the research we defined the term physical self-concept and presented some recent research in the field of physical self-concept in relation to physical activities for adolescents. We empirically researched the connection of weight status and sport activities to the physical self-concept of adolescents. The empirical research is based on a random group of pupils (n=161), aged 9-15 (M = 11, 87, SD = 1, 90). The group consisted of 86 boys and 75 girls. The data was gathered using the Children and Youth Physical Self–Perception Profile questionnaire. We added additional questions concerning age, gender, weight, height, and sport activities. The statistical data was processed using descriptive and inferential statistics. We examined the influence that a pupil’s weight and physical activity have on determining the degree of their physical self-concept in particular and in general. We found that 76.4 % of the pupils have ideal weight, 21.1% are overweight and 2.5% are obese. We encountered some statistically distinctive differences in estimating the extensions of physical self-concept, such as endurance, physical appearance and global self-esteem. There were also distinctive differences in estimating the entire physical self-concept of pupils from the three weight groups. 159 of the pupils surveyed are regularly active in sports: 113 do sports for recreation and 46 do sports for both recreation and competition. We managed to prove the existence of statistically distinctive differences among the pupils who are involved in sports for recreation and those who are involved for recreation and competition. These differences were found in the following categories: sport competence, endurance, strength and physical self-concept as a whole. We found that pupils with ideal weight and who are involved in competitive sports have a higher physical self-concept than pupils who are overweight or obese and are involved in sports only for recreation.